Multidrug resistance and high virulence genotype in uropathogenic Escherichia coli due to diffusion of ST131 clonal group producing CTX-M-15: an emerging problem in a Tunisian hospital - Ferjani, Sana; Saidani, Mabrouka; Ennigrou, Samir; Hsairi, Mohamed; Slim, Amine Faouzi; Ben Boubaker, Ilhem Boutiba (Folia microbiologica, 2014)
A collection of 201 Escherichia coli strains isolated from urine of patients in a Tunisian hospital between January 2006 and July 2008 was studied. Microbial identification was done by conventional methods, and antibiotic susceptibility with disk diffusion method was performed according to the Clinical Laboratory and Standards Institute guidelines. Detection of extended-spectrum beta-lactamase (ESBL) was performed by double-disk synergy test (DDST) and identification was done by PCR and sequencing. ESBL-producing isolates were subjected to molecular typing by random amplified polymorphic DNA (RAPD) and ST131 detection by PCR. Four phylogenetic groups (A, B1, B2 and D), 18 virulence genes and CTX-M group were individualized using PCR. Statistical analysis was done by Pearson χ2 test and Mann-Whitney U test. The strains were recovered primarily from urology (28%), maternity (19%) and medicine (16%) wards. Antibiotic resistance rates were ampicilin (72.1%), nalidixic acid (41.8%), ciprofloxacin (38.8%), gentamicin (23.9%) and cefotaxime (17.4%). Thirty-one of cefotaxime-resistant isolates (n = 35) had a positive DDST and harboured bla CTX-M-15 gene. Twenty of them (64.5%) belonged to the ST131 clone and showed the same RAPD DNA profile. Ciprofloxacin- and cotrimoxazole-susceptible isolates were significantly associated with phylogenetic group B2, whereas isolates that were resistant to these molecules were associated with B1 and D phylogenetic groups, respectively. Virulence genes were significantly more frequent among ciprofloxacin- and cotrimoxazole-susceptible strains than those resistant to these antibiotics. However, CXT-M-15-producing isolates were associated with many virulence genes. Isolates concomitantly susceptible to the three antimicrobials agents (ciprofloxacin, cefotaxime and cotrimoxazole) were significantly associated with group B2 and high virulence score, whereas isolates with resistance patterns especially those including resistance to ciprofloxacin belonged predominantly to B1 phylogroup and haboured few virulence genes. The emergence of virulent and multidrug-resistant E. coli is a concerning development that deserves close attention in our institution.
Keywords: Drug Resistance, Multiple, Bacterial; infekce močového ústrojí; lidé; Escherichia coli Infections; Virulence; antibakteriální látky; Female; infekce spojené se zdravotní péčí; beta-laktamasy; beta-Lactamases; virulence; uropatogenní Escherichia coli; Tunisia; Humans; Urinary Tract Infections; Genotype; Anti-Bacterial Agents; Microbial Sensitivity Tests; fylogeneze; mikrobiální testy citlivosti; Uropathogenic Escherichia coli; Tunisko; Cross Infection; mužské pohlaví; ženské pohlaví; genotyp; Male; mnohočetná bakteriální léková rezistence; Phylogeny; infekce vyvolané Escherichia coli